ATPase Cycle and DNA Unwinding Kinetics of RecG Helicase - Toseland, Christopher P.; Powell, Ben; Webb, Martin R. (PLOS ONE, 2012)
The superfamily 2 bacterial helicase, RecG, is a monomeric enzyme with a role in DNA repair by reversing stalled replication forks. The helicase must act specifically and rapidly to prevent replication fork collapse. We have shown that RecG binds tightly and rapidly to four-strand oligonucleotide junctions, which mimic a stalled replication fork. The helicase unwinds such DNA junctions with a step-size of approximately four bases per ATP hydrolyzed. To gain an insight into this mechanism, we used fluorescent stopped-flow and quenched-flow to measure individual steps within the ATPase cycle of RecG, when bound to a DNA junction. The fluorescent ATP analogue, mantATP, was used throughout to determine the rate limiting steps, effects due to DNA and the main states in the cycle. Measurements, when possible, were also performed with unlabeled ATP to confirm the mechanism. The data show that the chemical step of hydrolysis is the rate limiting step in the cycle and that this step is greatly accelerated by bound DNA. The ADP release rate is similar to the cleavage rate, so that bound ATP and ADP would be the main states during the ATP cycle. Evidence is provided that the main structural rearrangements, which bring about DNA unwinding, are linked to these states.